The fat mass and obesity related gene polymorphism influences the risk of rejection in heart transplant patients - Hubacek, Jaroslav A; Vymetalova, Jevgenija; Lanska, Vera; Dlouha, Dana (Clinical transplantation, 2018)
Heart transplantation is a relatively common treatment for end-stage heart failure. The major complication of heart transplantation is organ rejection. Epigenetic could play a role in the pathogenesis of organ rejection, and the FTO gene is a mediator of DNA methylation. We analyzed a tagging FTO SNP rs17817449 in both donor and recipient DNA obtained through 370 heart transplantations. Recipient FTO genotypes were not associated with either type of rejection or with the general increase in the risk of rejection. When compared with patients without a history of rejection, carriers of transplanted hearts with the FTO TT genotype exhibited a significantly increased risk (P = 0.02) of suffering from both types of rejection in comparison to carriers of hearts with at least one G allele (OR; 95% CI = 2.56; 1.15-5.69). Our results suggest that the donor, but not the recipient, FTO genotype could be a significant predictor of acute rejection in heart transplant patients.
Keywords: Polymorphism, Single Nucleotide; Humans; transplantace srdce; lidé středního věku; rejection; rejekce štěpu; následné studie; Graft Rejection; jednonukleotidový polymorfismus; Female; rizikové faktory; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; přežívání štěpu; Genotype; lidé; Heart Transplantation; Postoperative Complications; pooperační komplikace; ženské pohlaví; Male; Middle Aged; fat mass and obesity related gene; prognóza; single nucleotide polymorphism; heart transplantation; genotyp; gen pro FTO; mužské pohlaví; Graft Survival; Prognosis; Follow-Up Studies; Risk Factors